2017
DOI: 10.1177/1553350617692202
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Irreversible Electroporation: Safety and Efficacy of Next-Generation Irreversible Electroporation Adjacent to Critical Hepatic Structures

Abstract: Irreversible electroporation (IRE) is a nonthermal ablation modality employed to induce in situ tissue-cell death. This study sought to evaluate the efficacy of a novel high-frequency IRE (H-FIRE) system to perform hepatic ablations across, or adjacent to, critical vascular and biliary structures. Using ultrasound guidance H-FIRE electrodes were placed across, or adjacent to, portal pedicels, hepatic veins, or the gall bladder in a porcine model. H-FIRE pulses were delivered (2250 V, 2-5-2 pulse configuration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…2 H-FIRE consists of the delivery of bursts of short bipolar pulses (1-5 ls pulse length) instead of the 70-100 ls monopolar pulses typically used in IRE, and has been successfully applied to treat solid tumors with minimal muscle contractions. 29,35,42,43,51 The electric fields required to kill cells with H-FIRE are significantly higher than in conventional IRE protocols, 38,39 but when moving from monopolar IRE waveforms to bipolar H-FIRE bursts, the excitation thresholds of peripheral nerves increase even more significantly than the thresholds for cell death. 26 Thus, it is possible to minimize muscle contractions while maintaining treatment efficacy with H-FIRE.…”
Section: Introductionmentioning
confidence: 99%
“…2 H-FIRE consists of the delivery of bursts of short bipolar pulses (1-5 ls pulse length) instead of the 70-100 ls monopolar pulses typically used in IRE, and has been successfully applied to treat solid tumors with minimal muscle contractions. 29,35,42,43,51 The electric fields required to kill cells with H-FIRE are significantly higher than in conventional IRE protocols, 38,39 but when moving from monopolar IRE waveforms to bipolar H-FIRE bursts, the excitation thresholds of peripheral nerves increase even more significantly than the thresholds for cell death. 26 Thus, it is possible to minimize muscle contractions while maintaining treatment efficacy with H-FIRE.…”
Section: Introductionmentioning
confidence: 99%
“…For example, muscle contractions with HF-IRE pulses were much less noticeable than with 100 μs long monopolar pulses in experiments on rabbit liver 33 ,57 ,58. Even in the absence of cardiac synchronization and paralytics, only minor muscle twitch was recorded in one out of 24 cases59 ,60 when treating porcine liver. Sano et al observed that HF-IRE waveforms reduced the intensity of muscle contractions in comparison with traditional IRE pulses on ex-vivo porcine model34 and in in vivo murine tumor 46.…”
Section: Discussionmentioning
confidence: 96%
“…In a first human study on high-frequency irreversible electroporation of prostate cancer, only a small amount of muscle relaxant was needed, and there were no visible muscle contractions during the pulse delivery process 36. Additionally, the histological analysis in in vivo porcine experiments indicates that with HF-IRE rapid and reproducible ablation in the liver can be achieved, while preserving gross vascular/biliary architecture 60. The mechanism for decreased muscle contractions is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Recently, high-frequency IRE has also been shown to be effective for hepatic ablation in a porcine model. 33 , 34 The first clinical trial using IRE was performed on tumors in the kidney, 35 and several studies have followed describing treatment of tumors in internal organs such as liver, lung, and pancreas as a treatment that seems safe and feasible. 36 38 Irreversible electroporation has been shown to be used for tissue destruction, and normal tissue seems to also be affected.…”
Section: Irreversible Electroporationmentioning
confidence: 99%